Fecal Retention in Overactive Bladder (OAB) in Children: Perspective of a Pediatric Gastroenterologist - Su Jin Jeong (Korean Society of Pediatric Nephrology, 2015)
Coexisting voiding and bowel dysfunction in children are common in the clinic. The idea that overactive bladder (OAB) and constipation arise from one single pathophysiology has been reinforced in many studies. In Korea, a nationwide multicenter study conducted in 2009 showed that overall prevalence of OAB in children, 5-13 years of age, was 16.59% and this number has increased more recently. The initial step to manage coexisting fecal retention and OAB in children is to characterize their bowel and bladder habits and to treat constipation if present. Although diagnosing constipation in children is difficult, careful history-taking using the Bristol Stool Form Scale, and a scoring system of plain abdominal radiography, can help to estimate fecal retention more easily and promptly. Non-pharmacological approaches to manage functional constipation include increasing fluids, fiber intake, and physical activity. Several osmotic laxatives are also effective in improving OAB symptoms and fecal retention. Additionally, correction and education in relation to toilet training is the most important measure in treating OAB with fecal retention.